PERBANDINGAN KADAR ZINC PADA PERSALINAN PRETERM DAN KEHAMILAN NORMAL - Delvina, Visti; Amir, Arni; Ermawati, Ermawati (LLDIKTI Wilayah X, 2018)
The Comparative Zinc Levels in Preterm Labor and Normal PregnancyABSTRACT Preterm labor occurs between 20 weeks and before 37 weeks of pregnancy. It is indicated by regular contractions of the uterus and it may cause the thinning and flattening of the cervix. Preterm labor also causes the high rates of perinatal morbidity and mortality. Deficiency zinc during pregnancy can stimulate the preterm labor. The design of this reseacrh was a comparative cross sectional study. It was conducted in Rasidin District Hospital, Siti Rahmah Hospital and Biomedical Laboratory, Faculty of Medicine, Andalas University, Padang on Februari 2017 to June 2018. There were 50 samples in this reseach. It was selected by consecutive sampling. The samples were divided into two groups: preterm labor and normal pregnancy. Zinc levels are examined by the ELISA method. Then, the data were analyzed by using the t test. The results of this reseach showed that the mean zinc level in the preterm labor group was 12.22 ± 0.41 μmol / L and 13.96 ± 0.64 μmol / L of the mean zinc level in the normal pregnancy group with P= 0.000. Moreover, statistical test inffered that there was significant difference between zinc levels in preterm labor and normal pregnancy. In short, it can be concluded that zinc levels group in the preterm labor were lower than the normal pregnancy group. Keywords: Zinc, Preterm Labor Perbandingan Kadar Zinc Pada Persalinan Preterm dan Kehamilan NormalABSTRAK Persalinan preterm adalah persalinan yang terjadi antara 20 minggu dan sebelum 37 minggu kehamilan yang ditandai adanya kontraksi teratur dari uterus yang dapat menyebabkan penipisan dan pendataran serviks. Persalinan preterm menyebabkan tingginya angka morbiditas dan mortalitas perinatal. Defiseiensi zinc selama kehamilan dapat menstimulasi terjadinya persalinan preterm. Desain penelitian ini adalah cross sectional komparatif, penelitian dilakukan di RSUD Rasidin, RSI Siti Rahmah dan Laboratorium Biomedik Fakultas Kedokteran Universitas Andalas Padang pada bulan Februari 2017 – Juni 2018. Jumlah sampel sebanyak 50 yang dipilih secara consecutive sampling, yang dibagi menjadi dua kelompok yaitu persalinan preterm dan kehamilan normal. Kadar zinc diperiksa dengan metode ELISA. Data dianalisa menggunakan uji t test. Hasil penelitian rerata kadar zinc pada kelompok persalinan preterm 12,22 ± 0,41 µmol/L dan rerata kadar zinc pada kelompok kehamilan normal adalah 13,96 ± 0,64 µmol/L dengan nilai p 0,000. Secara statistik terdapat perbedaan yang bermakna antara kadar zinc pada persalinan preterm dan kehamilan normal. Kesimpulan, kadar zinc pada kelompok persalinan preterm lebih rendah daripada kelompok kehamilan normal. Kata Kunci : Zinc, Persalinan Preterm